Efficacy of extended, comprehensive outpatient cardiac rehabilitation on cardiovascular risk factors: A nationwide registry. (27th August 2020) - Reich, Bernhard; Benzer, Werner; Harpf, Hanns; Hofmann, Peter; Mayr, Karl; Ocenasek, Helmuth; Podolsky, Andrea; Pokan, Rochus; Porodko, Michael; Puelacher, Christoph; Sareban, Mahdi; Traninger, Heimo; et al.
Abstract : Aim: Cardiac rehabilitation (CR) is a key component of the treatment of cardiac diseases. The Austrian outpatient CR model is unique, as it provides patients with an extended professionally supervised, multidisciplinary program of 4–6 weeks of phase II (OUT-II) and 6–12 months of phase III (OUT-III) CR. The aim of this analysis was to assess the efficacy of the Austrian outpatient CR model using a nationwide registry. Methods: Data of all consecutive patients ( N  = 7560) who completed OUT-II and/or OUT-III between 1 January 2005 and 31 December 2015 were entered prospectively into a registry. OUT-III patients were analyzed separately according to whether the preceding phase II was performed as outpatient (OUT-II/OUT-III, N  = 2403) or in-patient (IN-II/OUT-III, N  = 2789). All patients underwent assessment of anthropometry, resting blood pressure, lipid profile, fasting blood glucose, exercise capacity, quality of life, anxiety and depression. Results: During OUT-II, patients significantly improved their metabolic risk factor profile and increased exercise capacity by 14.3%. OUT-II/OUT-III patients achieved an additional increase in exercise capacity by 10%, further improvement in high-density lipoprotein (HDL) and stabilization of the remaining risk factors. IN-II/OUT-III patients increased their maximal exercise capacity by 18.4% and there was improvement in blood pressure, HDL, low-density lipoprotein and glucose levels. Conclusion: Extended, professionally supervised, multidisciplinary outpatient CR in a large nationwide registry of consecutive patients consistently improved maximal exercise capacity and relevant modifiable cardiovascular risk factors beyond effects seen after IN- or OUT-II alone.